Survey on big data security in various applications - Sethy, Ambica; Ray, Abhishek (International Journal of Engineering and Technology, 2018)
The present era has become a digital world, which has been serving the mankind in each and every sector. Due to this, a lot of varied data is used and stored across the digital world. To handle this tremendous varied data, the concept of big data plays a vital role. Data and big data are two sides of a single coin. Digitization has been made possible along with the growth of data through Big data. This leads to creation of many security concerns in Big Data applications. This paper presents a review on some of the existing security and privacy issues on different big data application domains and triggered some new additional V’s like visualization plus vulnerability, which has been correlated with the security and privacy issues on those domains. This paper also focuses on that application area which has not taken security and privacy issues of big data into consideration. We have also found some new issues that could become possible threats for the protective data in various applications.